Shock wave-boundary layer interactions at the supersonic flow around three-dimensional configurations - Панов, Євген Миколайович; Карвацький, Антон Янович; Лелека, Сергій Володимирович; Лазарєв, Тарас Валерійович; Педченко, Анатолій Юрійович (Eastern-European Journal of Enterprise Technologies, 2015)
The study suggests that the problems of interactions of turbulent flows at the supersonic flow around aircraft elements be solved by numerical analysis methods aided by a mathematical model that is based on the system of the Reynolds-averaged Navier-Stokes equations. The system includes the k-ω SST turbulence model for viscous compressible medium (with two scalar equations of turbulent kinetic energy and relative velocity of its dissipation with the modification that takes into account the transfer of shear stress). The paper presents applied testing and verification of the model along with examples of the problems on supersonic flows around a flat wall and a sphenoid superstructure as well as a perpendicular gas stream. We have identified physical characteristics of interactions between the condensation wave and the boundary turbulent layer, which manifest themselves in the formation of a complex structure of disconnecting and connecting zones of a boundary turbulent layer, which are characterized by respective lines of separation and joining on the wrap surface. The solutions adequately reflect the pattern of the supersonic flow of a compressible medium, condensation waves and vortex zones that are commonly observed during field studies. The comparative analysis of the results of numerical modeling and experimental data confirms the applicability of the mathematical model for complex tasks of the supersonic gas-dynamic state.